2020
DOI: 10.1038/s41598-020-76591-4
|View full text |Cite
|
Sign up to set email alerts
|

Developmental differences in the intestinal microbiota of Chinese 1-year-old infants and 4-year-old children

Abstract: The microbiota profile of children changes with age. To investigate the differences in the gut microbiota profile of 1- and 4-year-old children, we collected fecal samples and sequenced the V3–V4 hypervariable region of the 16S rRNA gene via high-throughput DNA sequencing. From phylum to species level, the microbiota underwent significant changes with age. The abundance of phyla Proteobacteria and Actinobacteria declined with age, whereas phyla Firmicutes and Bacteroidetes increased with age and dominated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 54 publications
1
16
0
Order By: Relevance
“…However, the composition of the microbiome changes continuously with age. Comparison of the microbiome composition in infants and in 4-year-old children revealed the reduction in the population of phyla Proteobacteria and Actinobacteria accompanied by the increase in phyla Firmicutes and Bacteroidetes in the gut of the older children (Guo et al 2020).…”
Section: Alteration In Gut Microbiota With Agingmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the composition of the microbiome changes continuously with age. Comparison of the microbiome composition in infants and in 4-year-old children revealed the reduction in the population of phyla Proteobacteria and Actinobacteria accompanied by the increase in phyla Firmicutes and Bacteroidetes in the gut of the older children (Guo et al 2020).…”
Section: Alteration In Gut Microbiota With Agingmentioning
confidence: 97%
“…In general, as the microbiome functionality differs between infants and adults, therefore the microbial profiles are adapted in response, e.g., while the microbiota involved in amino acid and vitamin metabolism dominates in infants gut, these microbes will be slowly replaced by microbiota participated in fat metabolism with age (Guo et al 2020).…”
Section: Alteration In Gut Microbiota With Agingmentioning
confidence: 99%
“…Researchers have reported that healthy adults have significantly higher diversity of their gut microbiomes than young children in the United States (Ringel-Kulka et al, 2013). Similarly, a detailed comparison of the intestinal microbiota of 1-year-old infants and 4-year-old children in China revealed that the species richness, evenness, and diversity of the intestinal microbiota were significantly lower in the 1-year-olds (Guo et al, 2020). These aging effects not only occur in gut microbiota but also in other parts of the symbiotic microbiota.…”
Section: Community Structures Of Gut Microbiota Differed Between Juve...mentioning
confidence: 99%
“…and more complex composition compared to adults, suggesting ongoing microbial development [30]. On the contrary, a 2019 study reported a cohort of 281 school-aged children between six and nine years old to have an adult-like alpha diversity and a similar functional repertoire to that of adults [33], whilst a 2020 study reported four-year olds to have an adult-like gut microbiota, with significantly increased levels of adult gut-dominating phyla Bacteroidetes and Firmicutes and decreased infant-gut phyla Actinobacteria and Proteobacteria [34].…”
Section: The Development Of the Infant Gut Microbiotamentioning
confidence: 99%